Kinesin family member 23, regulated by FOXM1, promotes triple negative breast cancer progression via activating Wnt/β-catenin pathway - Zhi Li (Journal of Experimental & Clinical Cancer Research, 2022)
Abstract Background Triple negative breast cancer (TNBC) is highly malignant and has a worse prognosis, compared with other subtypes of breast cancer due to the absence of therapeutic targets. KIF23 plays a crucial role in the tumorigenesis and cancer progression. However, the role of KIF23 in development of TNBC and the underlying mechanism remain unknown. The study aimed to elucidate the biological function and regulatory mechanism of KIF23 in TNBC. Methods Quantitative real-time PCR and Western blot were used to determine the KIF23 expression in breast cancer tissues and cell lines. Then, functional experiments in vitro and in vivo were performed to investigate the effects of KIF23 on tumor growth and metastasis in TNBC. Chromatin immunoprecipitation assay was conducted to illustrate the potential regulatory mechanisms of KIF23 in TNBC. Results We found that KIF23 was significantly up-regulated and associated with poor prognosis in TNBC. KIF23 could promote TNBC proliferation, migration and invasion in vitro and in vivo. KIF23 could activate Wnt/β-catenin pathway and promote EMT progression in TNBC. In addition, FOXM1, upregulated by WDR5 via H3K4me3 modification, directly bound to the promoter of KIF23 gene to promote its transcription and accelerated TNBC progression via Wnt/β-catenin pathway. Both of small inhibitor of FOXM1 and WDR5 could inhibit TNBC progression. Conclusions Our findings elucidate WDR5/FOXM1/KIF23/Wnt/β-catenin axis is associated with TNBC progression and may provide a novel and promising therapeutic target for TNBC treatment.